Dependent development : the alliance of multinational, state, and local capital in Brazil - Evans, Peter B. (Princeton, N.J. : Princeton University Press, 1979)
The book focuses on the relationship among multinational corporations, local private entrepreneurs, and state owned enterprises that have been developed in Brazil in the 1970$1 (Bs.s
Includes bibliographical references: p. [331]-351 and index.
lje 14/05/2018
Loans
Keywords: Capital; International business enterprises; Government business enterprises